2016
DOI: 10.17306/j.afs.2016.3.25
|View full text |Cite
|
Sign up to set email alerts
|

The eff ect of thermal treatment on antioxidant capacity and pigment contents in separated betalain fractions

Abstract: Background. Increased consumption of fruits and vegetables signifi cantly reduces the risk of cardio-vascular disease. This benefi cial eff ect on the human organism is ascribed to the antioxidant compounds these foods contain. Unfortunately, many products, particularly vegetables, need to be subjected to thermal processing before consumption. The aim of this study was to determine the eff ect of such thermal treatment on the antioxidant capacity and pigment contents in separated fractions of violet pigments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
0
17
0
8
Order By: Relevance
“…Pasteurization significantly ( P < 0.05) affected the betalain content of beet puree with a 12.8–13.9% and 10.1–11.1% reduction of betacyanins and betaxanthins, respectively depending upon the film type, with larger losses in the high OTR film. Other studies have reported losses of between 6–81% and 13–73% in betacyanins and betaxanthins, respectively, during thermal treatments of red beets and beet products . According to Herbach et al, betaxanthins are more sensitive to thermal treatment than betacyanins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasteurization significantly ( P < 0.05) affected the betalain content of beet puree with a 12.8–13.9% and 10.1–11.1% reduction of betacyanins and betaxanthins, respectively depending upon the film type, with larger losses in the high OTR film. Other studies have reported losses of between 6–81% and 13–73% in betacyanins and betaxanthins, respectively, during thermal treatments of red beets and beet products . According to Herbach et al, betaxanthins are more sensitive to thermal treatment than betacyanins.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported losses of between 6-81% and 13-73% in betacyanins and betaxanthins, respectively, during thermal treatments of red beets and beet products. [20][21][22][23] According to Herbach et al, 4 betaxanthins are more sensitive to thermal treatment than betacyanins. However, in the present study, betaxanthins showed higher retention than betacyanins.…”
Section: Beet Pureementioning
confidence: 99%
“…The highest percentage of decarboxylated derivatives was found in the peel. This phenomenon could be a result of exposing red beetroots to light and temperature, causing the transformation of betacyanins into decarboxylated forms (Mikołajczyk-Bator & Pawlak, 2016;Wybraniec, 2005).…”
Section: The Profile and Content Of Betalains In Red Beet Productsmentioning
confidence: 99%
“…Their presence incites the fluorescence property of betaxanthin [4,38]. From the findings of Mikołajczyk-Bator and Pawlak [41], thermal degradation of red-violet pigments was three times lower than yellow color given compounds despite the antioxidant capacity of the latter, which tends to be higher after heat treatments.…”
Section: Betalainsmentioning
confidence: 99%
“…Those neo-derivatives are of interest due to their yellow color appearance derived from thermal degradation of Beta vulgaris and Opuntia species betanin [37]. Most degradation processes of betacyanin are isomerization, deglycosylation, dehydrogenation, hydrolysis, and decarboxylation [5,37,41]. Betalamic acid which is core structure of betalain, (b) Amino acid which conjugates with betalamic acid to derive betaxanthin, (c) Yellow color giving betaxanthin, (d) Vulgaxanthin I which is a derivative of betaxanthin, (e) cyclo-DOPA which condenses with betalamic acid to give betacyanin, (f) Red-violet color giving betacyanin, and (g) Betanin which is a derivative of betacyanin [2,5,14,27,28,37,42].…”
Section: Betalainsmentioning
confidence: 99%